The STUDIES ON AVIFAUNAL DIVERSITY AT MANCHAR LAKE, JAMSHORO,SINDH, PAKISTAN. - Memon, Quratulain; Sheikh, Prof Dr Kalsoom (Dialogue Social Science Review (DSSR), 2024)
ABSTRACT Background: Manchar Lake is much important wetland which is providing various Environmental services essential for avifaunal species nesting and visiting the area of lake. Ecosystem services include stabilization of shorelines, purification of water, storm protection, storage of water and support to various animal and plant species. Objectives: The main objective of present research study is to assess the biodiversity of avifaunal species visiting the lake, their IUCN status, distinguish between resident and migratory species. Methods: Field visits were conducted on different intervals of every month to record the biodiversity and prevalence of birds. Results: A total number of 140 specimens were recorded and identified into ten diverse species belonging to eight families including Ardeidae, Anatidae, Laridae, Accipitridae, Anhingidae, Laridae, Rallidae, and Glareolidae. Important findings of the proposed research are from total recorded specimens, five species (50%) were recorded as resident and five (50%) were Migratory. The feeding habits observed were predominantly carnivorous (6 species, 60%), followed by omnivorous (2 species, 20%), insectivorous (1 species, 10%), and grainivorous (1 species, 10%). Seasonal Prevalence: The highest prevalence of recorded species occurred in January, February, and March, with the lowest richness observed in June and July. Conclusion: The study concluded that Manchar Lake is experiencing significant pollution due to runoff from agricultural fields, residential areas, and other sources. This pollution, combined with factors such as massive hunting, climatic changes, seasonal fluctuations, and decreasing food resources, has led to a decline in bird populations at the lake. Keywords: Avifauna, diversity, fluctuation, species, declining, shorelines.